Limits of Metacognitive Prompts for Confidence Judgments in an Interactive Learning Environment - Klar Maria; Buchner Josef; Kerres Michael (Open Education Studies, 2024)
Metacognitive activities are reported to improve learning but prompts to support metacognition have only been investigated with mixed results. In the present study, metacognitive prompts for confidence judgments were implemented in a learning platform to provide more insights into their effectiveness and their limits. Comparing the prompted group (n = 51) with the control (n = 150), no benefits of the prompts are seen: Performance is not better with prompts, and there is no improvement in metacognitive accuracy over time within the prompted group. Notably, half of the prompted group did not use the metacognitive prompts as intended. Alternative ways to integrate such prompts are discussed.